2023
DOI: 10.3389/fncir.2023.1120410
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial focused ultrasound selectively increases perfusion and modulates functional connectivity of deep brain regions in humans

Abstract: BackgroundLow intensity, transcranial focused ultrasound (tFUS) is a re-emerging brain stimulation technique with the unique capability of reaching deep brain structures non-invasively.Objective/HypothesisWe sought to demonstrate that tFUS can selectively and accurately target and modulate deep brain structures in humans important for emotional functioning as well as learning and memory. We hypothesized that tFUS would result in significant longitudinal changes in perfusion in the targeted brain region as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The seemingly inconsistent tFUS effects between Cain et al (2021b) [54] and Kuhn et al (2023) [55] were discussed as likely due to the differences in the vasculature and connectivity of the thalamus. In a single-participant study by Schafer et al (2021) [56], tFUS applied to the unilateral entorhinal cortex increased the cerebral blood perfusion in the targeted area, consistent with the findings of Kuhn et al (2023) [55]. In a study by Nakajima et al (2022) [22], suppressive tFUS to the subthalamic nucleus (STN) and the anterior putamen of the right basal ganglia were also investigated, respectively, both of which resulted in impairments in stopping performance during a stop-signal task.…”
Section: Disorder Of Consciousness (Doc)mentioning
confidence: 91%
See 2 more Smart Citations
“…The seemingly inconsistent tFUS effects between Cain et al (2021b) [54] and Kuhn et al (2023) [55] were discussed as likely due to the differences in the vasculature and connectivity of the thalamus. In a single-participant study by Schafer et al (2021) [56], tFUS applied to the unilateral entorhinal cortex increased the cerebral blood perfusion in the targeted area, consistent with the findings of Kuhn et al (2023) [55]. In a study by Nakajima et al (2022) [22], suppressive tFUS to the subthalamic nucleus (STN) and the anterior putamen of the right basal ganglia were also investigated, respectively, both of which resulted in impairments in stopping performance during a stop-signal task.…”
Section: Disorder Of Consciousness (Doc)mentioning
confidence: 91%
“…It also decreased perfusion throughout the cerebrum for at least several minutes following tFUS, as observed by using arterial spin labeling (ASL). In another study employing ASL and BOLD-fMRI, Kuhn et al (2023) [55] found that tFUS directed at the right amygdala and left entorhinal cortex selectively increased perfusion and BOLD responses in the targeted brain region and its functional connectivity to other regions. The seemingly inconsistent tFUS effects between Cain et al (2021b) [54] and Kuhn et al (2023) [55] were discussed as likely due to the differences in the vasculature and connectivity of the thalamus.…”
Section: Disorder Of Consciousness (Doc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the number of human-based studies is rapidly growing. While many of them enlighten the processes which underpin FUS (increased cortical excitability [11][12][13][14][15] through GABA inhibition [16]; brain activity in the target region could be either increased [12,[17][18][19][20][21] or decreased [22]; altered functional connectivity [13,16,17,23,24]; increased NMDA-dependent synaptic plasticity [25]), others already moved into more complex research on behavioural changes (sensory discrimination [18,[26][27][28]; motor inhibition [11,[29][30][31]; reaction time [32]; approach and withdrawal behaviours [33]; mood [24]; pain [34]; fear [35]), and the more audacious focused on pathological conditions (epilepsy[36-38]; Alzheimer's disease [39] and other dementia [40]; consciousness disorders [41]; tremor [42]; Parkinson's disease [43]; depression [44]; chronic pain [45]). However, FUS outcomes remain complex to interpret due to an incomplete understanding of the mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%
“…Low-intensity transcranial focused ultrasound (tFUS) is increasingly deemed as a promising noninvasive neuromodulation technology for modulating brain activity. Studies have shown that tFUS unequally modulates activities of neuronal subpopulations [1][2][3], and affects neural pathways [4][5][6][7] by delivering pulsed mechanical energy to target brain areas with high spatial specificity and deep penetration.…”
Section: Introductionmentioning
confidence: 99%